A CONTENT ANALYSIS OF “ENGLISH FOR NUSANTARA” FOR SEVENTH JUNIOR HIGH SCHOOL - Hidayah, Vita Tri Kurniawati; Zahro, Syifa’ Khuriyatuz (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
Textbooks are essential in the teaching and learning process, offering structured guidance to achieve the goals of language learners. This study aimed to evaluate the English textbook